Potensi Ekstrak Bunga Rosella (Hibiscus Sabdariffa L.) Sebagai Pengawet Alami yang Diaplikasikan pada Daging Ayam Segar Pengganti Formalin - Restu Tjiptaningdyah, Kejora Handarini (AGROKNOW, 2014)
Abstract. Contamination by microbial pathogens on fresh chicken meat cold store render the product less safe. Extreme effort that many people do actually use formaldehyde as a preservative, which clearly have a negative impact on human health. Rosella flowers are plants that have antibacterial activity against Escherichia coli, Staphylococcus aureus and Salmonella typhi on agar media.Â Thus necessary to study aimed to determine the ability of rosella flower extracts in lowering the amount of microbial contamination indigineous (total microbial aerofilik, total coliform, and total salmonella sp) found in fresh chicken meat and inhibit its growth during storage refrigerator temperature.The first phase of the study is manufacturing rosella extract and the second stage is to apply the roselle extract on fresh chicken meat. Applications on fresh chicken meat is done is: A1: sterile distilled water submersion for 30 minutes (control), A2: immersion rosella flower extract 0.20 g / ml for 30 minutes, A3: 0:25 rosella flower extract immersion g / ml for 30 minutes , A4: 00:30 rosella flower extract immersion g / ml for 30 minutes, A5: 1% formalin soaking for 30 minutes, and then all samples were stored at refrigerated temperatures for storage of 0, 5, 10, and 15 days. The parameters measured were total microbial aerofilik, total Coliform, and total Salmonella sp.The results showed that free during storage 0 day total microbial parameters aerofilik, total coliform, salmonella sp total value exceeds a specified limit contamination SNI, ie respectively: 3.6 x 107, 3.5 x 10 3, 6.2 x 10 2 CFU / g. Rosella extracts can inhibit the growth of indigenous microbial contaminants than controls, both in the total microbial aerofilik, coliform, salmonella sp, 0 to15 days during storage, the various treatment A2, A3 & A4. A4 is the best inhibitory concentration (roselle extract 0.30 g / ml), as it can provide the highest value of inhibition compared to the treatment of A2 and A3. Fresh chicken meat with rosella extract treatment, has the shelf life to 10 days of storage.Kata kunci: rosella, pengawet alami, daging ayam segar